Effect of Attentional Focus Instructions on Spatial Memory in Children - Fatemeh Mirakhori; Elahe Arabameri; Fazlolah Bagherzadeh; Rasool Hemayattalab (University of Tehran, 2020)
The purpose of this study was to examine the effect of attentional focus instructions on spatial memory in children.Thirty girl students with the mean age from 7 to 12 years were selected by convenience sampling from elementary schools in Tehran. Participants were randomly divided into three attentional focus groups (internal, external, control). Participants in the internal focus group were asked to focus their attention on the movements of their hand, whereas participants in the external focus group were asked to focus their attention to the movement path and target. Control group participants received no focus instructions. Acquisition phase lasted five consecutive days. The instrument used for measuring spatial memory was linear movement apparatus (LM-01 model). Analysis of Covariance and Bonferoni tests were used at p